Relationship between Physical Activity and HbA1c Levels at Made Health Center (Universitas Pendidikan Indonesia, 2025)
One of the non-communicable diseases that has become a global concern is diabetes mellitus, a metabolic disease characterized by hyperglycemia. An accurate examination to measure blood glucose levels is HbA1c test, which measures blood glucose levels in the last three months. The Global Physical Activity Questionnaire is a tool to measure the intensity of physical activity. Physical activity, in moderate and vigorous intensity, is an important management to control blood glucose levels. This research aimed to determine the relationship between physical activity and HbA1c levels in the general medicine unit at the Made Public Health Center in Surabaya City. This research used an analytical observational study with a cross-sectional design. The population of this study was an eligible population with 30 samples. The examination of HbA1c levels used venous blood samples of respondents, while the examination of physical activity used the global physical activity questionnaire. Based on univariate analysis, most of the respondents, namely 21 respondents (70,0%), had mild physical activity and 24 respondents (80,0%) had uncontrolled HbA1c levels. Fisher’s Exact Test analysis showed a p-value of 0.049 p-value (0.05). It concludes that there is a relationship between physical activity and HbA1c levels in the general medicine unit at the Made Public Health Center in Surabaya City.